SEJARAH DAN MODERNISASI TNI ANGKATAN UDARA: IMPLIKASI TERHADAP PERTAHANAN NASIONAL - Makhbul Hudori, Raudho; Arifin, Zainul; Apdilla, Raya; Maftuh Sujana, Ahmad (Berajah Journal, 2025)
This article examines the history of the Indonesian National Air Force (Tentara Nasional Indonesia Angkatan Udara, TNI AU) following Indonesia’s proclamation of independence in 1945. Established in April 1946, the TNI AU emerged amid significant political, social, and military challenges during the early years of Indonesia’s struggle to maintain sovereignty. The formation and development of TNI AU were marked by limited resources and complex dynamics, including the repurposing of captured aircraft and the integration of former colonial military personnel. The article highlights key phases in TNI AU’s evolution, such as its strategic role in major battles like the Five-Day Battle in Semarang and efforts to secure and operate airbases previously controlled by Japanese forces. Moreover, the TNI AU faced continuous political and social challenges, requiring adaptation to changing military doctrines and modernization efforts through international training and procurement of advanced technology. Beyond combat roles, the TNI AU has been actively involved in humanitarian missions and disaster relief, underscoring its broader national significance. This study uses qualitative methods supported by primary interviews, historical documents, and archival data to provide a comprehensive understanding of TNI AU’s contributions to Indonesia’s defense and state-building processes post-independence. The findings demonstrate the crucial role of TNI AU in safeguarding national sovereignty and advancing Indonesia’s military capabilities.